THE CONCENSUAL INTERACTION BETWEEN A TRADITIONAL VILLAGE AND HOTEL INVESTORS - I Wayan Kiki Sanjaya; I Nyoman Darma Putra; I Wayan Ardika; I Gede Mudana (Pusat Penelitian dan Pengabdian kepada Masyarakat (P3M) Politeknik Negeri Bali, 2018)
This article examines the agreement and consensus between Kedewatan as a pakraman (a traditional village) in Ubud, Bali, Indonesia and hotel investors. It is done as a qualitative approach and analyzed by using two theories of critical cultural studies, namely the communicative action of Jurgen Habermas and the theory of hegemony by Antonio Gramsci. Data are obtained through observation, document studies, and in-depth interviews. The results of this study found three consensuses between Kedewatan villagers and hotel investors. First, the formal legal investment consensus that has an agreement in the form of the contribution of the hotel investor during the investment in Kedewatan Village. Second, the social consensus is the agreement of Kedewatan and hotel investors to employ the local community of Kedewatan Village as hotel employees in accordance with their competencies. Third, the cultural consensus is the agreement of both parties to appreciate the local culture and wisdom of local people to be adopted by the hotel investors who set up their business in Kedewatan Village